Respons Pertumbuhan dan Produksi Bawang Merah Terhadap Pemberian Pupuk Bokashi - Fitri, Annisa; Zulfahmi, Reza; Tiara, Dede; Adzania Lestari, Mustika; Purnama Sari, Hevia; Aulia Putrantri, Desti (J-Plantasimbiosa, 2025)
Shallot (Allium ascalonicum L.) is an important horticultural commodity that contributes significantly to Indonesia's economy. However, its production declined in 2022–2023 compared to 2021. Fertilization plays a key role in improving soil fertility and supplying nutrients for optimal plant growth. This study aimed to assess the growth and yield response of the Brebes shallot variety to various doses of bokashi fertilizer and to determine the most effective dose. The experiment used a Randomized Complete Block Design (RCBD) with one factor: bokashi dosage, consisting of six treatments—B0 (control), B1 (1 kg/m²), B2 (1.5 kg/m²), B3 (2 kg/m²), B4 (2.5 kg/m²), and B5 (3 kg/m²). Each treatment was replicated four times with ten plants per replication, totaling 280 experimental units. The results indicated that bokashi application significantly affected leaf length, leaf diameter, bulb length, bulb diameter, fresh and dry bulb weight, as well as total yield per clump. The highest growth and yield were observed at the 3 kg/m² dosage. Thus, bokashi at 3 kg/m² is considered the most effective dose for improving the growth and productivity of the Brebes shallot variety.